Hak dan Kewajiban Warga Negara dalam Islam : Analisis terhadap Piagam Madinah dan Konstitusi Modern - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Muhammad Irfan Al Ghiffari; Fanny Fatekhah Saputri; Nurul Khasanah (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
The rights and obligations of citizens in Islam are fundamental aspects that emphasize the balance between individual responsibilities and the protection provided by the state. This study analyzes the concept of citizens' rights and obligations in Islam based on the Charter of Medina and modern constitutions. The Charter of Medina, a historical document drafted by Prophet Muhammad (PBUH), provides an early depiction of citizenship principles in Islam, such as equal rights, religious freedom, and the duty to maintain national security. Meanwhile, modern constitutions, although based on secular or nationalist principles, still adopt some universal values aligned with Islamic teachings, such as social justice, human rights, and political participation. This study employs a qualitative method with a historical and normative analytical approach to compare how these two documents define citizens' rights and obligations. The findings reveal that the Charter of Medina established the foundation for an inclusive concept of citizenship that emphasizes cooperation among various societal groups. On the other hand, modern constitutions expand individual rights through more detailed legal instruments. However, challenges arise when there is an imbalance in the implementation of rights and obligations, particularly in Muslim-majority countries that apply Islamic law partially or selectively. This study employs a qualitative method with a historical and normative analytical approach to compare how these two documents define citizens' rights and obligations. The findings reveal that the Charter of Medina established the foundation for an inclusive concept of citizenship that emphasizes cooperation among various societal groups. On the other hand, modern constitutions expand individual rights through more detailed legal instruments. However, challenges arise when there is an imbalance in the implementation of rights and obligations, particularly in Muslim-majority countries that apply Islamic law partially or selectively. In conclusion, there is continuity between the principles found in the Charter of Medina and modern constitutions in guaranteeing citizens' rights and obligations. However, effective implementation requires a balance between Islamic values and democratic principles to ensure that citizens' rights are protected without neglecting their obligations to the state and society.